Efecto citotóxico de cadmio y plomo en Vicia faba “haba” en condiciones de laboratorio - Mogollon De Rivero, Patricia Rossy Angélica Milagros Carlota (2019)
In the present research work, cytotoxic effect of cadmium and lead in apical cells of the secondary roots of Vicia faba "bean" seedlings was determined. For this, we worked with 27 seedlings of Vicia faba "haba" with 10 days of vegetative development and individually each covered by cotton and placed in disposable cups, embedded with distilled water free of lead and cadmium metals. Four solutions of cadmium and four of lead plus a control solution were prepared, with three repetitions for each treatment; The imbibition of each metal was performed for 3 days. The apexes were cut by immersing in 1N hydrochloric acid, then stained with 2% acetic Orcein and observed under a microscope; the mitotic index was calculated and cellular (chromosomal) abnormalities were observed. An analysis of variance (ANOVA) and multiple range test was performed using the method of significant minimum difference HSD TUKEY. The results showed that there is a statistically significant difference between treatments (P> 0.05). The concentration of cadmium where there was a higher MI was 1 ppm, while for lead it was 5ppm. Observing cell abnormalities: in anaphase, showing bridges between chromosomes, nuclear lesions and chromosome breakage in anaphase and metaphase. The results showed that cadmium was the metal that caused a greater cytotoxic effect in the cells of the mitotic division of Vicia faba "haba", this is a species that offers an experimental model to evaluate the cytotoxic effect, in this case of cadmium and lead, which generated cellular (chromosomal) abnormalities at all concentrations.